2019
DOI: 10.1371/journal.pone.0223724
|View full text |Cite
|
Sign up to set email alerts
|

Single-cell qPCR demonstrates that Repsox treatment changes cell fate from endoderm to neuroectoderm and disrupts epithelial-mesenchymal transition

Abstract: A definitive endodermal cell lineage is a prerequisite for the efficient generation of mature endoderm derivatives that give rise to organs, such as the pancreas and liver. We previously reported that the induction of mesenchymal definitive endoderm cells depends on autocrine TGF-β signaling and that pharmacological blockage of TGF-β signaling by Repsox disrupts endoderm specification. The definitive endoderm arises from a primitive streak, which depends largely on TGF-β signaling. If the TGF-β pathway is bloc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 34 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Previous studies have demonstrated that the process of EMT is dependent on autocrine TGF-β signaling ( 31 , 32 ). Thus, in the present study, it was hypothesized that RepSox regulates the expression of E-cadherin and N-cadherin by regulating the BMP family.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that the process of EMT is dependent on autocrine TGF-β signaling ( 31 , 32 ). Thus, in the present study, it was hypothesized that RepSox regulates the expression of E-cadherin and N-cadherin by regulating the BMP family.…”
Section: Resultsmentioning
confidence: 99%
“…Promotes neuronal differentiation of NPCs (Yan et al, 2021) PDGF Neurotrophic factor and promotor of cell survival involved in NPCs differentiation (Funa and Sasahara, 2014) QVD-OPh Inhibitor of caspases, anti-apoptotic (Kuželová et al, 2011) Repsox TGF-β pathway inhibitor. Increases neuroepithelial markers levels and promotes neuronal differentiation (Li and Huang, 2019) Retinoic acid Metabolic product of vitamin A involved in NPCs differentiation into specific types of neurons (Maden, 2007) SP600125 Inhibitor of the c-Jun N-terminal kinase (JNK) signaling pathway. This leads to a reduction in stemness and promotes cellular differentiation (Semba et al, 2020) Selenium Oxidative stress and other damaging factors protector (Van et al, 2003) Transferrin Neuroprotector, part of the antioxidant defense system, iron metabolism (Van et al, 2003) TTNPB Agonist of RA receptor subtype important for ensuring stem cell reprogramming into neuronal-like cells (Das and Pethe, 2021) Valproic Acid Inhibitor of histone deacetylase, leading to changes in chromatin structure and gene expression that favor neuronal differentiation (Phiel et al, 2001;Vukićević et al, 2015) Vitamin C Neuroprotective effects, antioxidant (May, 2012), enhancer of the expression of genes involved in neurogenesis, maturation, and neurotransmission (Shin et al, 2004) Y27632 Rho-kinase inhibitor, which indirectly inhibits the ERK signaling pathway promoting stem cells survival and differentiation (Kamishibahara et al, 2016;Fu et al, 2018) Cavaleiro et al 10.3389/fnmol.2023 Frontiers in Molecular Neuroscience 09 frontiersin.org 5.…”
Section: Isoxazole9mentioning
confidence: 99%